Families, Powered On Improving Family Engagement in Early Childhood Education Through Technology - Daugherty, Lindsay (RAND Corporation, 2014)
The authors describe the barriers that hinder family engagement with early childhood education and the ways in which technology may afford new opportunities to overcome these barriers-empowering families to become better educators at home, and strengthening connection and communication between school and home.